Digital Twin BIM Management System of Storage Tanks Based on BIM and UE4 - ZENG Qingda; HU Ting; WANG Huang; WANG Yuanyuan; QIN Jing (Renmin Zhujiang)
In order to improve the digitalization and smart water operation and maintenance management of storage tanks,and to achieve the digital and intelligent control,scheduling and management of storage tanks,taking the largest storage tank at the end of Longgang River in Shenzhen as the research object,based on the BIM model with full-professional collaborative forward design,this paper develops the digital twin BIM management system by the BIM software based on the Autodesk platform and the advanced game engine Unreal engine in current industry,with high-fidelity rendering capabilities,close-to-real visualization effects,BIM+GIS available and real-time reading,and interactive communication of various sensor information in the storage tank through secondary development for improving the the real-time interaction and intelligent control of equipment,and based on this,develops functional modules such as rainfall prediction,pedestrian and vehicle traffic,equipment management,and operation management to successfully extend the BIM technology to the operation and maintenance management stage of the storage tank,and give full play to the greater role of BIM,which provide reference for future smart operation and maintenance projects.